Physicochemical and Rheological Properties of Composite Shark Catfish (Pangasius pangasius) Skin Collagen Films Integrated with Chitosan and Calcium Salts. Issue 3 (16th November 2015) - Elango, Jeevithan; Robinson, Jeya Shakila; Geevaretnam, Jeyasekaran; Rupia, Emmanuel J.; Arumugam, Varatharajakumar; Durairaj, Sukumar; Wenhui, Wu
Abstract: Collagen, collagen–chitosan (C1), collagen–calcium acetate (C2) and collagen–chitosan–calcium acetate (C3) films were prepared from shark catfish ( P angasius pangasius ) skin, and were investigated for their mechanical and functional properties. Collagen was characterized as type I and contained three identical chains. C3 film had higher tensile strength (10.4 MPa) and Young's modulus (570 MPa). Composite films had low swelling rates and solubility and lasted for 6 days before complete biodegradation. Fourier transform infrared spectra suggested that the interactions of collagen with chitosan and calcium salts affected the secondary structure and molecular order of collagen, particularly the triple helical structure. Scanning electron microscopy micrograph of collagen films depicted the formation of spindle‐like structures with chitosan, granules with calcium acetate salts and porous structures in C3 films. Therefore, it was concluded that the collagen films had better mechanical, functional and in‐vitro biodegradation properties by the addition of calcium and chitosan. These results demonstrate the potential application of composite collagen films from shark catfish skin in biomedical and pharmaceutical industries. Practical Applications: To reuse fish‐processing waste for biomedical materials, multicomposite collagen films were prepared from shark catfish skin and examined for their physicofunctional and mechanical properties. The purified collagen was combined with calcium and chitosan to improve the film properties. These results suggest that collagen films had better mechanical, in‐vitro biodegradation and functional properties by the addition of calcium and chitosan. Accordingly, the prepared multicomposite fish collagen films could be suitable materials in biomedical and pharmaceutical industries as alternatives to mammalian collagen films.